The Prevalence and the Clinical Importance of os vesalianum pedis - Uğuz Gençer, C; Tetiker, H; Koşar, M I; Çullu, N (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: Os vesalianum pedis (OVP) is a rare accessory bone of the foot located at the base of the fifth metatarsal bone. It is usually asymptomatic and incidentally seen on radiographs. When symptomatic, it manifests itself with lateral foot pain. OVP, which can become symptomatic as a result of traumatic injuries, can also be confused with fracture. The aim of this study is to determine the prevalence and morphometric characteristics of OVP in the Turkish population. MATERIAL AND METHODS: Radiographic images of 5268 individuals aged 16 years and older (mean 39.65±17.21) who completed ossification of the fifth metatarsal bone were evaluated for OVP. Of the cases included in the study, 44.8% were female and 55.2% were male. The general and sex-based prevalence of OVP was calculated, and morphometric measurements were done. RESULTS: OVP prevalence in the Turkish population was found to be 0.15% regardless of sex. OVP prevalence was calculated to be 0.24% in men and 0.04% in women. CONCLUSIONS: Anatomy, radiology, orthopedics and emergency medicine physicians are frequently encountered with foot disorders in clinical and educational practices. It is important to keep in mind the rare presence of OVP (0.15%), in the preliminary diagnosis. KEY WORDS: os vesalianum pedis, accessory ossicle, foot, radiography.
Keywords: Turecko; Prevalence; Clinical Relevance; mladiství; Radiography; klinická relevance; Middle Aged; mužské pohlaví; prevalence; Turkey; Adult; mladý dospělý; metatarzální kosti; Young Adult; ženské pohlaví; radiografie; Humans; Metatarsal Bones; lidé středního věku; dospělí; Female; Adolescent; lidé; Male